Mitral Valve Surgery - Bonser, Robert S.; Pagano, Domenico; Haverich, Axel.; SpringerLink (Online service) (London : Springer London, 2011)
An appreciation of atrioventricular valve surgical anatomy reveals that they are much more than simple valves, opening and closing in response to pressure changes. The structural interrelationship of the valves of the heart and the dynamic mechanisms involved in their function are fundamental in optimizing valve performance, and are dependent upon an intricate multifaceted central cardiac complex. Mitral Valve Surgery presents a detailed background of the mitral valve, its pathology, evaluation, repair and replacement from a range of experts in the field, providing a detailed reference for clinicians in cardiology, cardiac surgery, interventional cardiology, and related fields. The Editors have designed the book to be a comprehensive and systematic review including current practical information and guidance. As we look to the future, mitral valve surgery will continue to evolve and attempting to maximize patient outcome such injury will become increasingly important. This book provides the fundamental background information to fuel interest, initiate novel prevention, refine surgical and therapeutic strategies, and inform the investigator how to develop and design their research study.
Anatomy, pathology & natural history of mitral valve disease -- Surgical anatomy of mitral & tricuspid valve -- Pathology & classification -- Non-ischaemic mitral regurgitation:assessment natural history & evidence for surgery -- Ischaemic mitral regurgitation:assessment, natural history & the impact of interventions -- Mitral valve repair & replacement techniques -- Indications & techniques. Conservation of leaflets & chordal apparatus -- Principles of mitral valve repair:restoring the coaptation -- Principles of mitral valve repair: the edge-to-edge technique -- How to assess & repair the Barlow mitral valve -- Assessment & management of systolic anterior motion (SAM) -- Surgical management of ischaemic mitral regurgitation -- Mitral valve repair in cardiomyopathies -- Mitral stenosis: natural history & intervention -- Atrial fibrillation in mitral valve disease -- Non-surgical management -- Surgical management -- Tricuspid valve in mitral valve disease -- Tricuspid regurgitation: assessment, natural history & intervention.
Keywords: Medicine; Radiology, Medical; Critical care medicine; Internal medicine; Cardiology; Emerging infectious diseases; Heart -- Surgery; Medicine & Public Health; Cardiac Surgery; Cardiology; Infectious Diseases; Imaging / Radiology; Internal Medicine; Intensive / Critical Care Medicine